Nanomaterials in Cosmetics: Regulatory, Quality & Safety Assessment - Kumari, Poonam; Pandita, Deepti; Poonia, Neelam; Lather, Viney (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2017)
Background: The field of nanotechnology is growing tremendously in vast areas with 13% nano-based products in cosmetic industry. The use of nanomaterials (NMs) in cosmetics formulations for different applications has led to safety concerns globally with aspects related to skin which comes in direct contact and indirectly to the environment with respect to waste management, and is the major issue that needs attention. Objectives: This article will deliberate on the current status of regulatory and safety guidelines for the use of NMs in cosmetics. The need for harmonization globally, by the regulatory authorities and the trend of where it is heading in future towards safety and quality assessment of cosmetics and their ingredients is also highlighted. Discussion: The use of NMs in cosmetics may enhance or inhibit the skin absorption of ingredients. Its use has raised concerns in EU, US, Canada, Japan, etc. The current evidences so far suggest that the NMs used in cosmetic formulations possess no risk to human health particularly skin; rather than they possess the multiple benefits to human health such as protection from the UV radiation which can cause skin cancer. Though few researches have suggested potential risks that have not been confirmed yet. An active debate and discussion regarding the potential risk of NMs in cosmetics has been performed by regulatory agencies and steps are being taken by several regulatory bodies towards harmonization.
Keywords: harmonization